The core expression is similar to this
y = (f(x) for x in L if f(x) is not None)
There are a lot of variations on the filter. The point is that the function appears twice in the above expression.
We have a number of alternatives.
- y = filter(None, f(x) for x in L)
- y = filter(None, map(f, L))
- y = (x for x in map(f, L) if x)
- y = (x for x in (f(y) for y in L) if x is not None)
- y = (val for x in L for val in (f(x),) if val is not None)
My preference is two steps, even though I don't really have a good reason for this.
y2 = (f for f in y1 if f)
Like this:
y = (f(x) as val for x in L if val is not None)
The as clause binds the f(x) to val so that it can be used in the if clause.
Summary: Interesting.
No comments:
Post a Comment
Note: Only a member of this blog may post a comment.